Sustainable de-growth in business modelling - Puhakka, Maarit (My University, 2018)
The poor global environmental protection and the overuse of the natural resources during the last decades has led to unprecedented increase of greenhouse gases in the atmosphere of our planet causing climate chance that is threatening all life on Earth. One of the sustainability efforts to tackle this huge challenge of mankind is the idea of sustainable de-growth which is calling for a drastic change in the relationships of the natural environment, the people and their economic activities. Thus, this thesis examines the possibility of integrating the key values and characteristics of sustainable de-growth into the value proposition, value delivery, value creation as well as value capture elements of a viable business model. The theoretical framework of this study builds on the values and principles of sustainable de-growth as well as theories of sustainable business modelling and sustainable value creation. To gather the empirical findings, a single case study with semi-structured interviews and a business modelling workshop were conducted at Helsinki Metropolitan Area Reuse Centre Ltd which has claimed to be the first business in Finland practising de-growth As an outcome of this study, a sustainable de-growth value framework, a table with the sustainable de-growth business characteristics compared with the four modules of a business model as well as a sustainable de-growth business modelling flowsheet were developed to assist the innovation process of a genuinely sustainable business model. The value framework visualises the need to radically change our mindset in terms of the relationship between people and their business activities and the environment. Whereas the sustainable de-growth business characteristics and the flowsheet can be used as practical and easy to use tools for managers of all kinds of enterprises to evaluate and develop their business models towards genuine environmental and social sustainability.
Keywords: sustainable de-growth; sustainable business models; second-hand; reuse centre; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|